2007
DOI: 10.1111/j.1540-8167.2007.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Left Ventricular Ejection Fraction Following Atrioventricular Junction Ablation and Pacing for Atrial Fibrillation

Abstract: Methods/Results: We studied 286 patients with AF who underwent AVJ ablation and RVA pacing at our institution between 1990 and 2002. Patients were stratified into a short-term follow-up group (LVEF reassessed by echocardiography within a year after AVJ ablation, n = 134) and a long-term group (LVEF reassessed after a year, n = 152). Among all 286 patients (mean follow-up 20 months), we observed no change in mean LVEF after AVJ ablation and RVA pacing (48% before vs. 48% after, P = 0.42). Short-term follow-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 53 publications
2
42
0
1
Order By: Relevance
“…The antibody status of these patients was not reported, and it is possible that mechanisms other than ventricular dyssynchrony such as immune-mediated alterations in ventricular function may have contributed to LV dysfunction. 9 As shown by Chen et al, 15 most patients requiring ablation of the atrioventricular junction for atrial fibrillation do not develop deterioration in ventricular function with RV pacing, suggesting that ventricular dyssynchrony alone may not be responsible for worsening HF. ICAVB commonly occurs in children born to mothers with systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The antibody status of these patients was not reported, and it is possible that mechanisms other than ventricular dyssynchrony such as immune-mediated alterations in ventricular function may have contributed to LV dysfunction. 9 As shown by Chen et al, 15 most patients requiring ablation of the atrioventricular junction for atrial fibrillation do not develop deterioration in ventricular function with RV pacing, suggesting that ventricular dyssynchrony alone may not be responsible for worsening HF. ICAVB commonly occurs in children born to mothers with systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 86%
“…Although recent studies have reported pacing-induced ventricular remodeling and poor outcomes in patients with ICAVB, risk factors associated with the detrimental effect of pacing continue to be poorly defined. 8,9 Immune-mediated cardiomyopathy has been recognized in patients with a positive rheumatoid factor test result [12][13][14][15][16] and in infants born to mothers with antinuclear antibodies (ANAs). 12,[17][18][19][20] Thus, we hypothesized that the presence of ANA in adult congenital ICAVB patients may be associated with worse outcomes after pacemaker implantation.…”
Section: Clinical Perspective On P 1705mentioning
confidence: 99%
“…Although a single‐center retrospective study suggested that AVJA, followed by RV pacing, was not associated with an adverse impact on left ventricular (LV) ejection fraction,16 this was not confirmed by a randomized clinical trial, especially in patients with underlying LV dysfunction or symptomatic HF 4. Furthermore, the deleterious effect of RV pacing was mitigated by the use of biventricular pacing.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 286 patients at the Mayo clinic undergoing AVJ ablation with RV apical pacing, at a mean follow-up of 20 months, no significant change in LVEF was noted compared with baseline. 24 Additionally, the cumulative 10-year probability of HF hospitalization after AVJ ablation was only 8%. Similar findings were reported recently from a European single-center registry, which suggested that many patients with high-burden RV pacing maintain stable LVEF with a low incidence of new-onset HF.…”
Section: Discussionmentioning
confidence: 99%